Identification polypeptide biomarkers of porcine skin gelatin by two-dimensional electrophoresis - Mohd Amin, Aina; Ismail, Amin; Raja Nhari, Raja Mohd Hafidz; Che Man, Yaakob (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
The peptide composition of gelatin is known to vary very common that the electrophoretic pattern of gelatin from one source differs from another source even for the same raw material. Therefore, the present study aimed to use proteomics field to identify gelatin polypeptides biomarker for depending on the condition under which collagen is hydrolyzed. Hence, it is porcine skins. The polypeptides obtained for porcine skin gelatins can be used as reference in future to detect the origins of gelatin added in the processed food. We compared porcine skin gelatin samples obtained from three producers. Total average numbers of polypeptides of porcine skin gelatins from company A, B and C were 303 ± 2.8, 285.5 ± 3.5 and 270.5 ± 4.9 spots respectively. 10 biomarkers were identified and presented in all different companies. We also did a mixture of porcine and bovine skin gelatin to detect the presence of these 10 biomarkers. The level of adulteration that could be detected was as low as 1.0% w/w.